Tanggung Jawab Hukum Perdata atas Penggunaan Citra Publik Figur dalam Foto Buatan AI - Desi Patul Hotima; Diki Zukriadi (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2026)
This study aims to analyze civil liability arising from the use of public figures’ images in AI-generated photographs and to assess the adequacy of Indonesian civil law in providing legal protection for image rights. This research employs a normative legal method with statutory, conceptual, and socio-legal approaches. Data were collected through a literature-based study of primary and secondary legal sources and analyzed qualitatively using deductive legal reasoning. The findings indicate that the unauthorized use of public figures’ images in AI-generated photographs may be classified as an unlawful act (onrechtmatige daad) under Article 1365 of the Indonesian Civil Code. Consequently, perpetrators may be held civilly liable for compensation and other remedial measures aimed at restoring the violated rights of the affected individuals.